Provincializing Hegemonic Histories of Media and Communication Studies: Toward a Genealogy of Epistemic Resistance in Africa - Willems, Wendy (Communication Theory, 2014)
In the late 1990s and 2000s, a number of calls were made by scholars to “internationalize” or “dewesternize” the field of media and communication studies. I argue that these approaches have indirectly silenced a much longer disciplinary history outside “the West” that has not only produced empirical knowledge but has also actively challenged Western epistemologies. This article seeks to reinscribe the epistemological and historical foundations of media and communication studies in Africa. By framing the research of African media and communication scholars within the changing nature of knowledge production, shifting power relations between African nations, and the evolving role of African universities, I demonstrate how academic knowledge production is frequently driven and constrained by particular dominant social, political, and economic interests.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/comt.12043
Keywords: 1-Cinéma; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé